Living Near the Mines: Understanding the Multifactor Causes of Acute Respiratory Infection in Toddlers of Konawe Regency: Acute Respiratory Infection - Fitri Yanti; Ari Tjahyadi Rafiuddin (STIKes Mandala Waluya Kendari, 2026)
Background: Acute Respiratory Infection (ARI) is one of the leading causes of morbidity among children under five in Indonesia. Mining areas have a higher risk of ARI occurrence. This study aimed to analyze the relationship between epidemiological, environmental, behavioral, and health service factors and the incidence of ARI among children under five in the mining area of Morosi District, Konawe Regency. Methods: This research employed a cross-sectional design with a total of 118 mothers of children under five selected through purposive sampling. Data were analyzed using univariate analysis to describe frequency distributions and bivariate analysis using the Chi-square test. Results: The results showed an ARI prevalence of 75.4%. The presence of black mold (p-value = 0.003), type of house ventilation (p-value = 0.029), distance from the house to the industry (p-value = 0.020), and distance from the house to the main road (p-value = 0.037) were significantly associated with ARI. Household behavior of opening windows (p-value = 0.025) and the availability of a village health post (p-value = 0.001) were also significantly related to ARI incidence. Conclusion: It can be concluded that ARI incidence among children under five in the mining area of Morosi is influenced by environmental factors (ventilation and black mold), household behavior (window-opening habit), and access to primary health care facilities (village health post). ARI prevention efforts should focus on improving home environmental conditions, promoting clean and healthy living behaviors, and enhancing access to primary health services in mining areas.